A self-contained and integrated microfluidic nano-detection system for the biosensing and analysis of molecular interactions. Issue 9 (11th April 2022) - Xie, Xinwu; Ma, Jinbiao; Wang, Hao; Cheng, Zhen; Li, Tie; Chen, Shixing; Du, Yaohua; Wu, Jianguo; Wang, Can; Xu, Xinxi
Abstract : A self-contained and integrated microfluidic nano-detection system was developed, demonstrating excellent performance for biosensing and analysis of molecular interactions. Abstract : Traditional detection methods have shortcomings such as time-consumption and requirement of large instruments, which cannot meet the demands for on-site detection or analysis. Silicon nanowire-field-effect transistor (SiNW-FET) biosensors have the advantages of high speed, high sensitivity, strong specificity, and ease of integration. However, SiNW-FET biosensors also have some demerits: they are too sensitive, environmental factors such as light, temperature, and pH easily cause interference, and their performance uniformity needs to be calibrated in advance. In this work, we constructed a self-contained and integrated microfluidic nano-detection system containing a SiNW-FET biosensor for bio-detection and analysis. All analysis processes including liquid sample delivery, optical modulation, constant temperature control, signal amplification and data acquisition, and result display were automatically performed. In series tests including light-guided ones by analyzing various types of samples with an automatic sample injection mode, the system shows good stability and robustness. Its signal accuracy was verified using a commercial high-precision ammeter ( R 2 = 0.9988), too. The feasibility of the system for bio-detection was verified using simulant samples of the typical microorganism Mycobacterium tuberculosis with a limit of detection of 1.0 fg mL −1 . Furthermore, the process of the binding-dissociation of antibody–protein pairs was analyzed using the system, demonstrating the potential for molecular interaction analysis. This system is highly integrated, small in size, and easy to carry, which will be developed into a portable device for on-site bio-detection and analysis of molecular interactions to enable environmental testing, medical research, food and agricultural safety, military medicine, etc.